Advantages and limitations of current biomarker research: from experimental research to clinical application - Kim, Seung‑Hyun; Weiß, Christel; Hoffmann, Ursula; Borggrefe, Martin; Behnes, Michael; Akın, Ibrahim (Current pharmaceutical biotechnology, 2017)
Background: Biomarkers are indispensable tools for screening, diagnosis, and prognosis in cardiovascular diseases and their clinical application increases steadily. As cardiovascular diseases include various pathophysiological processes, no single biomarker, even natriuretic peptides, can be regarded as ideal fulfilling all necessary criteria for a comprehensive diagnostic or prognostic assessment revealing optimal clinical application. Hence, multi-marker approaches using different biomarkers reflecting different pathophysiologies were highlighted recently. Advances in biomedical technologies expanded the spectrum of novel blood-derived biomarkers, such as micro-RNA (miRNA) or “omics”- data potentially providing a more advanced knowledge about pathogenesis of cardiovascular disease. Conclusion: This review describes the advantages and limitations of blood circulating biomarkers with regard to proteins, metabolomics and transcriptional level both within single as well as multi-marker strategies. Moreover, their usefulness is focused on clinical decision-making in cardiovascular diseases.